EULAR evidence based recommendations for gout. Part I: Diagnosis. Report of a task force of the standing committee for international clinical studies including therapeutics (ESCISIT). Issue 10 (17th May 2006) - Zhang, W; Doherty, M; Pascual, E; Bardin, T; Barskova, V; Conaghan, P; Gerster, J; Jacobs, J; Leeb, B; Lioté, F; McCarthy, G; Netter, P; et al.
Abstract : Objective: To develop evidence based recommendations for the diagnosis of gout. Methods: The multidisciplinary guideline development group comprised 19 rheumatologists and one evidence based medicine expert, representing 13 European countries. Ten key propositions regarding diagnosis were generated using a Delphi consensus approach. Research evidence was searched systematically for each proposition. Wherever possible the sensitivity, specificity, likelihood ratio (LR), and incremental cost-effectiveness ratio were calculated for diagnostic tests. Relative risk and odds ratios were estimated for risk factors and co-morbidities associated with gout. The quality of evidence was categorised according to the evidence hierarchy. The strength of recommendation (SOR) was assessed using the EULAR visual analogue and ordinal scales. Results: 10 key propositions were generated though three Delphi rounds including diagnostic topics in clinical manifestations, urate crystal identification, biochemical tests, radiographs, and risk factors/co-morbidities. Urate crystal identification varies according to symptoms and observer skill but is very likely to be positive in symptomatic gout (LR = 567 (95% confidence interval (CI), 35.5 to 9053)). Classic podagra and presence of tophi have the highest clinical diagnostic value for gout (LR = 30.64 (95% CI, 20.51 to 45.77), and LR = 39.95 (21.06 to 75.79), respectively). Hyperuricaemia is a major risk factor for gout and may be a useful diagnostic marker when defined by the normal range of the local population (LR = 9.74 (7.45 to 12.72)), although some gouty patients may have normal serum uric acid concentrations at the time of investigation. Radiographs have little role in diagnosis, though in late or severe gout radiographic changes of asymmetrical swelling (LR = 4.13 (2.97 to 5.74)) and subcortical cysts without erosion (LR = 6.39 (3.00 to 13.57)) may be useful to differentiate chronic gout from other joint conditions. In addition, risk factors (sex, diuretics, purine-rich foods, alcohol, lead) and co-morbidities (cardiovascular diseases, hypertension, diabetes, obesity, and chronic renal failure) are associated with gout. SOR for each proposition varied according to both the research evidence and expert opinion. Conclusions: 10 key recommendations for diagnosis of gout were developed using a combination of research based evidence and expert consensus. The evidence for diagnostic tests, risk factors, and co-morbidities was evaluated and the strength of recommendation was provided.